(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The genesis and fertility of soils are determined by the processes of transformation, migration and accumulation of matter, energy and information. It is proved that these processes determine the intensity of the development of podzol formation in soils, gleying, and the soddy process. It is shown that it is more profitable to grow on more cultivated soddy-podzolic soils, from an energy point of view. Winter wheat, on less cultivated - perennial grasses. On less cultivated soils, there is a greater risk of crop failure under adverse weather conditions. It is proposed to carry out an information assessment according to the multiple correlation equations. It is proved that the information-energy assessment of soils is necessary for the correct characterization of the genesis and fertility of soils.